2021
DOI: 10.1002/csc2.20583
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of key agronomical traits in soybean through genomic prediction of superior crosses

Abstract: Predicted performance of crosses was compared to progeny persistence during selection.• Almost all crosses producing promising advanced lines were above average for predicted yield.• Crosses with below-average predicted yield produced no superior advanced lines.• Genomic prediction can help identify the crosses most likely to produce superior progeny.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…Here, using 3D-GBS, we showed that it is possible to produce a lower number of restriction fragments, well and uniformly distributed across the genome, to reduce the number of reads needed to provide sufficient read coverage to call genotypes efficiently. Here, we found that 100K reads is sufficient to conduct GS with 3D-GBS, and that is significantly lower compared to previous studies where GBS has been used (e.g., Qin et al [ 48 ] with ~ 3.3M reads/sample, Jarquín et al [ 27 ] with ~ 2.6M reads/sample and Jean et al [ 28 ] with ~ 1.2M reads/sample). Similarly, we estimated the optimal number of reads per sample for an efficient genotyping of bi- and multi-parent populations.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Here, using 3D-GBS, we showed that it is possible to produce a lower number of restriction fragments, well and uniformly distributed across the genome, to reduce the number of reads needed to provide sufficient read coverage to call genotypes efficiently. Here, we found that 100K reads is sufficient to conduct GS with 3D-GBS, and that is significantly lower compared to previous studies where GBS has been used (e.g., Qin et al [ 48 ] with ~ 3.3M reads/sample, Jarquín et al [ 27 ] with ~ 2.6M reads/sample and Jean et al [ 28 ] with ~ 1.2M reads/sample). Similarly, we estimated the optimal number of reads per sample for an efficient genotyping of bi- and multi-parent populations.…”
Section: Resultscontrasting
confidence: 60%
“…To estimate the gain of 3D-GBS over the standard GBS approach, we selected two studies conducted internally, using ApeKI-based GBS protocol and with the lowest number of reads per sample for GS [ 28 ] and QTL mapping [ 12 ]. In these study cases, based on the optimal number of reads/sample estimated previously, with the same population, experimental design and goal, the application of 3D-GBS for GS and QTL mapping would have led to similar results with a significant reduction in per-sample sequencing cost: ~ 92% (~ 1.2M vs 100K reads/sample) and ~ 86% (~ 1.4M vs 200K reads/sample), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To explore this question, Jean et al (2021) used genotypic and phenotypic information on a set of 350 lines to predict the mean performance of over 60,000 potential crosses for yield and maturity, two key traits of prime concern to soybean breeders. To assess the accuracy of these predictions, a subset of 101 crosses that had been performed and subjected to selection in the course of past breeding work was examined.…”
Section: Main Achievements Of the Soyagen Projectmentioning
confidence: 99%
“…The gray rectangles showcase crosses with above-average yield for a given maturity. Reproduced with permission from Jean et al (2021) .…”
Section: Main Achievements Of the Soyagen Projectmentioning
confidence: 99%
“…It aims to predict the phenotype of an individual based only on its genotype (Crossa et al 2017). Recently, the use of GS models to predict superior crosses has been explored in soybean with very promising results (Jean et al 2021). This approach relies on the production of a simulated set of progenies, with the number and location of recombination events (REs) on each chromosome being predicted based on the genetic distances between markers on a genetic map (Mohammadi et al 2015).…”
Section: Introductionmentioning
confidence: 99%